Hubungan Self Regulated Learning Dengan Prokrastinasi Akademik Pada Mahasiswa Keperawatan - Agustina, Putri; Hikmatul Qowi, Nurul; Ubudiyah, Masunatul (Jurnal Keperawatan Muhammadiyah, 2025)
Academic procrastination is a common issue among students, negatively impacting motivation, increasing stress levels, and leading to suboptimal academic performance. Self-regulated learning is regarded as an effective strategy to address this problem, as it encourages students to manage their learning process independently, including planning, implementation, and self-evaluation. This study aims to analyze the relationship between self-regulated learning and academic procrastination among nursing students. It employed an analytical correlation design with a cross-sectional approach. The study sample consisted of 124 students selected through stratified random sampling. The independent variable was self-regulated learning, while the dependent variable was academic procrastination. Data collection was conducted using the Academic Procrastination Scale (APS) questionnaire and a self-regulated learning scale questionnaire. Data analysis was performed using the Spearman rank test. The findings indicate that the majority of students exhibited a moderate level of self-regulated learning (96 students, 77.4%) and academic procrastination (96 students, 77.4%). Statistical analysis yielded a value of 0.000 (p < 0.05) with a correlation coefficient (r) = -0.397, indicating a negative relationship between self-regulated learning and academic procrastination among nursing students. These results suggest that students should develop a greater awareness of their academic responsibilities and set clear learning goals. Future research is recommended to explore the role of conscientiousness in academic procrastination.